Cooperation and competition between the default mode network and frontal parietal network in the elderly - Koshino, Hideya; Osaka, Mariko; Shimokawa, Tetsuya; Kaneda, Mizuki; Taniguchi, Seira; Minamoto, Takehiro; Yaoi, Ken; Azuma, Miyuki; Higo, Katsuki; Osaka, Naoyuki (Frontiers in Psychology, 2023)
Recent research has shown that the Default Mode Network (DMN) typically exhibits increased activation during processing of social and personal information but shows deactivation during working memory (WM) tasks. Previously, we reported the Frontal Parietal Network (FPN) and DMN showed coactivation during task preparation whereas the DMN exhibited deactivation during task execution in working memory tasks. Aging research has shown that older adults exhibited decreased functional connectivity in the DMN relative to younger adults. Here, we investigated whether age-related cognitive decline is related to a reduced relationship between the FPN and DMN using a working memory task during the execution period. First, we replicated our previous finding that the FPN and DMN showed coactivation during the preparation period, whereas the DMN showed deactivation during the execution period. The older adults showed reduced DMN activity during task preparation and reduced deactivation during task execution; however, they exhibited a higher magnitude of activation in the FPN than the young individuals during task execution. Functional connectivity analyses showed that the elderly group, compared to the young group, showed weaker correlations within the FPN and the DMN, weaker positive correlations between the FPN and DMN during task preparation, and weaker negative correlations between the FPN and DMN during execution. The results suggest that cognitive decline in the older adults might be related to reduced connectivity within the DMN as well as between the FPN and DMN.